Peran Kepala Desa Dalam Pembangunan Desa Di Desa Cikalong Kecamatan Cilamaya Wetan Kabupaten Karawang - Nuur Huda Pitriyana; Evi Priyanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
this research usually aims to find a realistic picture of the role of village government in development. The role is the first indication of the success or failure of the village head and village officials in carrying out their duties. In this study, the researcher used observation, interview and documentation techniques. The focus of this research is on the role of village leaders in development, with an emphasis on theory According to Henry Mintzberg, (1992), the role of leaders are: 1. The role of interpersonal relationships, in this case the functions are leadership role models, team builders, coaches, directors, consultants . 2. Function Informal role as observer, disseminator and spokesperson. 3. The role of decision makers, business functions, interrupt management, resource allocator and negotiator. The village head must again maximize his steps in making decisions and controlling the use of the funds used, so that they know exactly what the funds are used for.